12=m/7+3

Simple and best practice solution for 12=m/7+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12=m/7+3 equation:


m in (-oo:+oo)

12 = m/7+3 // - m/7+3

12-(m/7)-3 = 0

9-1/7*m = 0 // - 9

-1/7*m = -9 // : -1/7

m = -9/(-1/7)

m = 63

m = 63

See similar equations:

| 4(8x+6)=-7(3x-4)+5x | | 30=3(w-5)+6w | | 6Z/5+7=0 | | x+3x+3=9 | | 5(y+4)-8y=17 | | -s+3=5a | | -4/3+Y=0 | | Y=70-1 | | -3(t+5)+(4t+2-4)=8 | | -2u+4(u-2)=-12 | | u/2-5=-9 | | a^11/2a^3 | | 100x+25(x+3)+5(2x)=1830 | | z/7-6=-5 | | z/7-6=24 | | -6(a+3)= | | 1.9r+9.3=15 | | 1/3p-8-p=4 | | 2x-10+3x/4=-5 | | 4/7x7/9x3/7 | | h(t)=-16t^2+96t+8 | | 9+c/6=17 | | 21y=9-(19y-23) | | 2-(-a-8)-15=9 | | 18x=-6+8x-6x | | 2(7a+1)=2a-10 | | 3(16x+4)=3(34+x) | | 129=5(2a-1)+2a | | 4(3m-2)=16 | | -2(2s-4)-8=-2(8s+6)-3 | | 5x^2+2x+18=0 | | (33/2)-5 |

Equations solver categories